HUBUNGAN MUTU PELAYANAN DENGAN REVISIT INTENTION PASIEN RAWAT JALAN DI RUMAH SAKIT SIAGA AL MUNAWWARAH SAMARINDA - Andi Disyanataly; Sumarni Sumarni; Chaerunnisa AR; Ratno Adrianto; Eka Putri Rahayu (Jurnal Manajemen Kesehatan Indonesia, 2026)
The World Health Organization (WHO) reports that poor-quality healthcare in low- and middle-income countries contributes to approximately 8.4 million deaths annually, highlighting service quality as a critical determinant of patient safety and health system performance. Service quality influences patient satisfaction, trust, and revisit intention, particularly in outpatient care. This study aimed to examine the relationship between service quality dimensions and revisit intention among outpatients at Siaga Al-Munawwarah Hospital, Samarinda. A quantitative cross-sectional design was conducted from January 2025 to February 2026 involving 118 respondents selected using the Lemeshow formula and purposive sampling. Data were collected through a validated and reliable Likert-scale questionnaire measuring tangibles, reliability, responsiveness, assurance, empathy, and revisit intention, and were analyzed using univariate analysis and Fisher’s Exact test at a 95% confidence level (α=0.05). The results showed significant associations between reliability (p=0.004), tangibles (p=0.001), empathy (p=0.023), and responsiveness (p=0.000) with revisit intention, while assurance (p=0.313) was not significantly related. These findings indicate that reliability, physical evidence, empathy, and responsiveness play important roles in increasing outpatient revisit intention, whereas assurance tends to function as a basic expectation rather than a distinguishing factor in patients’ decisions to return. Keywords: Service Quality, Revisit Intention, Hospital Services.